Wastelands in the cradle of the country. The ideological spacialization of urban conflict (Buenos Aires, 1979–1982) (Estudios Sociales, 2024)
This article interrogates, from a materialist theory of discourse, the creation of a historical preservation area (U-24 district) in the city of Buenos Aires in 1979 and the controversy that it aroused in a dictatorial context marked by massive demolitions for construction of urban highways and widening of avenues. Through the study of discursive categories of spatialization of social conflict («wastelands» and «demolished houses»; «patios»; «neighborhood»; «modern building» / «towers») three theses are supported: 1) that, during the dictatorship, contradictory discursive formations existed that reflected heterogeneous relationships between city and time; 2) that these categories constitute ideological ways of allusion/elision of the social conflict, in a context of systematic displacement of popular sectors from the city center; 3) that these discursive categories allow us to observe a shift from a «modern»temporality to a «presentist» one.
Keywords: heritage; discourse; city of Buenos Aires; urban conflict